The value of inpatient music therapy for gynae-oncology palliative care in Singapore - Wong, Kayla C.; Magee, Wendy L.; Mun, Sylvia; Sim, Yu Zhen; Nair, Tanuja; Tewani, Komal (Frontiers in Psychiatry, 2025)
Gynae-oncologic cancer affects the female reproduction system. When cancer treatment can no longer offer a cure, palliative care becomes the focus. This study aimed to understand how music therapy is valuable for women undergoing inpatient gynae-oncologic palliative care in a Singapore hospital since current evidence demonstrated limited knowledge on supportive care for this population. Utilizing a modified grounded theory, participant interviews and therapist reflexive logs generated knowledge on how music therapy was valuable for this population. Women undergoing inpatient gynae-oncology palliative care in Singapore were recruited at a single acute hospital. Sixteen participants between the ages of 25 to 84 were purposively sampled. Emergent from data were two key phenomena representing participants’ perception of their music therapy session(s); (1) The Interpersonal and Intermusical Experiences in Music Therapy, (2) The Function of Music in Music Therapy. The presence of a music therapist who is culturally sensitive and reflexive in their practice was quintessential in connecting with and providing a non-judgemental space for the women to fully express appreciation of their lives, leading to the palliation of symptoms such as anxiety and low mood, while increasing focus and attention. This study offers insights into clinical care specifically for women through a multicultural lens. Music therapy is valuable in providing a comfortable space to address patients’ psychosocial and emotional needs such as providing a space to take a break from a difficult reality, celebrate life, and to process grief and other difficult feelings through verbal and musical means within just one to two sessions.